P2 Outbreak case definitions for extrinsic allergic alveolitis due to metalworking fluids. (16th November 2010) - Burton, CM; Burge, PS; Robertson, AS; Robertson, W; Pickering, CAC; Hendrick, DJ; Barber, CM
Abstract : Introduction: In 2003, a large outbreak of occupational lung disease (OLD) occurred in the Powetrain plant in Birmingham, which included 21 workers who met the case definition for extrinsic allergic alveolitis (EAA). The aim of this study was to assess the performance of the case definition used during this and other outbreaks, against best available clinical diagnosis. Methods: All available hospital clinical data (including follow-up) for 37 workers with a documented clinical suspicion of EAA during the outbreak investigation was reviewed by a panel meeting of 5 UK OLD specialists. A definite clinical EAA case was accepted if at least four of the five experts agreed. This opinion was compared with a range of case definitions previously used during UK and US outbreaks. Results: A definite clinical diagnosis of EAA was accepted for 14 of the 37 workers. The performance (level of agreement, sensitivity and specificity) of different EAA case definitions vs the specialist clinical opinion is shown in Abstract P2 Table 1 . Discussion: The EAA case definition used in the Powertrain outbreak (Robertson 2007) showed substantial agreement with expert clinical opinion, correctly classifying 30/37 workers, without missing any of the definite clinical EAA cases. The Fox and Dangman criteria also performed well, correctly classifying a similar proportion of workers, but missing 1 and 3 of the definite clinical EAA cases respectively.